Women's Inheritance Rights in Indonesia from the Perspective of the Triangular Concept of Legal Pluralism - Suharsono, Agus; Prasetyoningsih, Nanik; Usman, Sunyoto (El-Mashlahah, 2024)
Indonesia's plural legal system, which includes Islamic, customary, and national laws, often leads to disparities in women's inheritance rights, particularly when national and customary laws interact, frequently disadvantaging women. This study aims to analyze the inheritance rights of girls in Indonesia through the lens of Wermer Menski's triangular concept of legal pluralism. It Utilizing uses a doctrinal approach focusing on legislative frameworks, concepts, cases, and interpretations,. Then, the research relies on secondary data, including primary and secondary legal materials, to draw conclusions and make recommendations. The findings reveal that inheritance rights are typically reserved for sons in patrilineal societies, while daughters are excluded but may receive gifts from the inheritance. Customary law prioritizes family harmony in inheritance distribution, allowing dissatisfied parties to pursue legal action. However, judicial decisions at lower courts vary, with some adhering to customary law that denies daughters inheritance rights while others apply state law granting daughters equal rights. The Supreme Court's Cassation Decision Number 197K/Sip/1961 affirmed equal inheritance rights for daughters, a consistently upheld stance culminating in jurisprudence Number 3/Yur/Pdt /2018. Analyzing this development through Menski's legal pluralism model suggests that women's inheritance rights in Indonesia have evolved to from level- 2 to level- 4, recognizing international legal influences. Meanwhile, Level- 5 is not by Indonesian law because the element of religious law is removed and replaced with natural law. For Level 5 to follow Indonesian law based on the Almighty God, further research is still needed.